RsgA releases RbfA from 30S ribosome during a late stage of ribosome biosynthesis - Goto, Simon (Nature Publishing Group, 2011)
RsgA is a 30S ribosomal subunit-binding GTPase with an unknown function, shortage of which impairs maturation of the 30S subunit. We identified multiple gain-of-function mutants of Escherichia coli rbfA, the gene for a ribosome-binding factor, that suppress defects in growth and maturation of the 30S subunit of an rsgA-null strain. These mutations promote spontaneous release of RbfA from the 30S subunit, indicating that cellular disorders upon depletion of RsgA are due to prolonged retention of RbfA on the 30S subunit. We also found that RsgA enhances release of RbfA from the mature 30S subunit in a GTP-dependent manner but not from a precursor form of the 30S subunit. These findings indicate that the function of RsgA is to release RbfA from the 30S subunit during a late stage of ribosome biosynthesis. This is the first example of the action of a GTPase on the bacterial ribosome assembly described at the molecular level.